2016
DOI: 10.1097/md.0000000000005295
|View full text |Cite
|
Sign up to set email alerts
|

Response of mouse thymic cells to radiation after transfusion of mesenchymal stem cells

Abstract: Thymic lymphoma is a highly invasive and even metastatic cancer. This study investigated the effects of mesenchymal stem cells (MSCs) transfusion on cell cycle, cell proliferation, CD3 expression, mutation frequency of T cell receptor using mouse model of thymic lymphoma.C57BL/6J young mouse models of thymoma were injected with MSCs. Six months later, the thymus was taken for pathological examination and flow cytometry studies. The cells were labeled with anti-CD4, CD8, CD3, propidium iodide, or CFDA-SE, cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Apart from uncontrolled proliferation and apoptosis occurrence, tumour cells as well trigger impaired regulation of cell cycle. Cell circle interphase consists of G1, S and G2 phases, respectively, ensuring DNA synthesis preparation, DNA replication and mitosis preparation . Coptisine (0‐28.11 μmol/L, 24 hours; 0‐75 μmol/L, 48 hours) induced HCT‐116 cell cycle arrest in G1 phase as well as decreased expressions of CDK4, CDK2, cyclin E and cyclin C, which were key genes of G1/S phase …”
Section: Anti‐cancer Propertymentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from uncontrolled proliferation and apoptosis occurrence, tumour cells as well trigger impaired regulation of cell cycle. Cell circle interphase consists of G1, S and G2 phases, respectively, ensuring DNA synthesis preparation, DNA replication and mitosis preparation . Coptisine (0‐28.11 μmol/L, 24 hours; 0‐75 μmol/L, 48 hours) induced HCT‐116 cell cycle arrest in G1 phase as well as decreased expressions of CDK4, CDK2, cyclin E and cyclin C, which were key genes of G1/S phase …”
Section: Anti‐cancer Propertymentioning
confidence: 99%
“…Cell circle interphase consists of G1, S and G2 phases, respectively, ensuring DNA synthesis preparation, DNA replication and mitosis preparation. 29,30 Coptisine (0-28.11 μmol/L, 24 hours; 0-75 μmol/L, 48 hours) induced HCT-116 cell cycle arrest in G1 phase as well as decreased expressions of CDK4, CDK2, cyclin E and cyclin C, which were key genes of G1/S phase. 31,32 Similar anti-cancer property of coptisine was observed in liver 33,34 In the next study, authors revealed that coptisine and NCI•H1650 cells.…”
Section: Anti -C An Cer Propert Ymentioning
confidence: 99%